Draft (Revised) Sikkim Tenth Five Year Plan 2002-07 and Annual Plan 2002-03 Volume-I - Planning Commission (Planning Commission, 2002)
living in rural areas according to the 1991 Census . the rural character of the state “Our interest on the ecological front, our commitment to social justice, our strive for a high growth regime and our conviction to make Sikkim heaven on earth should all be reflected in both the national and State plans of the next five years. the higher the level of attainment we have, the higher will be the degree of happiness and tranquility in the State. Our Government is totally committed to this, dedicated to achieve this and will strive to come out with flying colours.
Planning and Development Department